The Psychology of rrganizational change : viewing change from the employee's perspective - Oreg, Shaul; Michel, Alexandra; By, Rune Todnem (Cambridge : Cambridge University Press, 2013)
In a rapidly changing world, with constantly shifting dynamics, organizational change may prove essential if businesses are to continue to succeed. The majority of research on organizational change adopts a macro outlook, focusing on strategic issues from the perspective of the organization and its management. In this volume we undertake a micro perspective, focusing on the individual and, more specifically, the importance of the employees and their reactions to organizational change. This focus expands our understanding of why change initiatives frequently fail. The Psychology of Organizational Change constitutes an essential resource for scholars, students, and practitioners in the field of organizational change and development who strive to understand how to make change work not only for the organization, but also for its members.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).